PERFORMATIVITAS LOKAL DALAM WACANA WABAH - Ansari, Isa (Institut Seni Indoensia Surakarta, 2021)
The purpose of this study was to determine the public’s response to the government policies in dealing with the COVID-19 outbreak. The forms of response that are the object of this research are performative forms uploaded on social media. The target of this research is an evaluation of government policies in dealing with the covid outbreak by observing the performative responses presented by the community. The method used is observation and interpretive interviews that rely on local knowledge. Through this method, this research can reveal three elements, the first is the aspect of performative forms, namely ritual forms, performance forms and short films. The second is the aspect of practical knowledge in the form of discourse. In this aspect of the discourse, it is known that the community concept of the corona virus is based on local knowledge. The meaning of the virus has expanded in accordance with the understanding developed by the local community which is sometimes related to the aspects of belief. The third is the performative response that contributes to the prevention of the spread of coronavirus and the recording of local knowledge in dealing with covid-19.Keywords: Performative, Local Knowledge, Covid-19, Pandemic